Gender income inequality among Vietnamese informal workers in the context of Covid-19 - Anh, Do Vu Phuong; Hue, Hoang Thi; Huy, Nguyen Quang; Hien, Pham Thi Thuc; Huyen, Nguyen Thi Thu; Anh, Pham Ngoc (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2022)
The paper examines gender income inequality of informal workers in the context of Covid-19 pandemic in Vietnam through the Theil’s L index, using The Labor Force Survey by the General Statistics Office for the first three quarters of 2021. The results indicate that gender income inequality triggers informal workers' income inequality. Furthermore, males are proved to contribute more to income inequality among informal workers. In addition, results after utilizing the Blinder-Oaxaca decomposition method show that personal, labor-employment and geographical characteristics are factors breeding informal workers’ gender income inequality. Based on the findings, the authors propose several suggestions to equilibrate their income distribution and lessen the gender income inequality of informal workers.